2012
DOI: 10.1177/0192623312468517
|View full text |Cite
|
Sign up to set email alerts
|

Toxicant-associated Steatohepatitis

Abstract: Hepatotoxicity is the most common organ injury due to occupational and environmental exposures to industrial chemicals. A wide range of liver pathologies ranging from necrosis to cancer have been observed following chemical exposures both in humans and in animal models. Toxicant-associated fatty liver disease (TAFLD) is a recently named form of liver injury pathologically similar to alcoholic liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD). Toxicant-associated steatohepatitis (TASH) is a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 158 publications
(218 reference statements)
6
178
0
4
Order By: Relevance
“…Most subjects within these cohorts were also overweight or obese, and the ACHS cohort was previously reported to have elevated prevalence of disease components of the metabolic syndrome, therefore, we expected to find increased prevalence of NASH, consistent with these reports, and we hypothesized that mechanism of hepatic injury would be consistent with TASH because of the toxicant exposure. Liver injury in 80% of ACHS and 73.8% of ACHS-II cases was associated with hepatocellular necrosis, a characteristic of TASH 83,84 but not of NASH, or ASH, which are associated with increased hepatocellular apoptosis…”
Section: The Individuals Comprising the Achs And Achs-ii Cohorts Are mentioning
confidence: 99%
See 2 more Smart Citations
“…Most subjects within these cohorts were also overweight or obese, and the ACHS cohort was previously reported to have elevated prevalence of disease components of the metabolic syndrome, therefore, we expected to find increased prevalence of NASH, consistent with these reports, and we hypothesized that mechanism of hepatic injury would be consistent with TASH because of the toxicant exposure. Liver injury in 80% of ACHS and 73.8% of ACHS-II cases was associated with hepatocellular necrosis, a characteristic of TASH 83,84 but not of NASH, or ASH, which are associated with increased hepatocellular apoptosis…”
Section: The Individuals Comprising the Achs And Achs-ii Cohorts Are mentioning
confidence: 99%
“…Because steatohepatitis has previously been associated with insulin resistance and systemic inflammation 83,84 , we anticipated that dysregulation in biomarkers of these conditions would be observed along with elevations in indicators of liver damage and death.…”
Section: 69mentioning
confidence: 99%
See 1 more Smart Citation
“…Among PCB congeners, PCB 153 ( Figure 1) is present at the highest levels [69]. Dr.Cave's group has been demonstrated that chronic PCB 153 exposure worsened obesity/NAFLD in mice fed a high fat diet (HFD), but had no pathologic effect in mice fed control diet (CD) [70]. To better understand the biochemical mechanisms underlying these observations, a comprehensive investigation using high throughput analysis such as metabolomics is necessary.…”
Section: Objectives Of This Dissertationmentioning
confidence: 99%
“…According to the prevailing two hit hypothesis [127], dietary factors such as excessive fat consumption contribute to the formation of fatty liver, which makes the liver susceptible to a second hit which promotes the progression to more severe liver injury. Several factors have been shown to mediate the progression from simple steatosis (fatty liver) to steatohepatitis (fatty liver with inflammation and cell death) [128] and environmental agents that activate these factors can contribute to the extent of liver injury [129,130]. For example, arsenic was recently shown to contribute to the progression of diet-induced fatty liver disease by increasing inflammatory mediators in mouse liver [131].…”
Section: Introductionmentioning
confidence: 99%